IMPLEMENTASI QARD AL-HASAN SEBAGAI MODEL MICROFINANCE (SURVEI PADA LEMBAGA KEUANGAN SYARIAH MIKRO DI KABUPATEN BOJONEGORO) - Abdul Azis Safii (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2016)
Qard Al-hasan are microfinance method that can be gain form zakat, infaq, & sadaqa that manage by Islamic microfinance institution. This research analyze the role played by Islamic practices of zakat, sadaqa, and el Qard Al-hasan in poverty alleviation and the project of development. In order for Islamic economic practices to be inclusive and sustainable, these practices need to be coordinated and specific goal must be attached to each form of Islamic economic practice. The aim for this research is to obtain the financing practices of Qardh Al-Hasan at microfinance institution at Bojonegoro. The research finds that most of the sharia financial institutions in Bojonegoro have not distributed qardh funding, while some who channel Qardh Al-Hasan who are not focused on financing and capitalization of micro-entrepreneurs, such as qardh funds are instead disbursed as CSR (Corporate Social Responsibility), Qardh Al-hasan also distributed in the form of credits that are solely devoted to employees of the Financial Institution